Butyrate Inhibits Osteoclast Activity In Vitro and Regulates Systemic Inflammation and Bone Healing in a Murine Osteotomy Model Compared to Antibiotic-Treated Mice. (10th December 2021) - Wallimann, Alexandra; Magrath, Walker; Pugliese, Brenna; Stocker, Nino; Westermann, Patrick; Heider, Anja; Gehweiler, Dominic; Zeiter, Stephan; Claesson, Marcus J.; Richards, R. Geoff; Akdis, Cezmi A.; Hernandez, Christopher J.; et al.
Abstract : Short-chain fatty acids (SCFAs) produced by the gut microbiota have previously been demonstrated to play a role in numerous chronic inflammatory diseases and to be key mediators in the gut-bone signaling axis. However, the role of SCFAs in bone fracture healing and its impact on systemic inflammation during the regeneration process has not been extensively investigated yet. The aim of this study was to first determine the effects of the SCFA butyrate on key cells involved in fracture healing in vitro, namely, osteoclasts and mesenchymal stromal cells (MSCs), and second, to assess if butyrate supplementation or antibiotic therapy impacts bone healing, systemic immune status, and inflammation levels in a murine osteotomy model. Butyrate significantly reduced osteoclast formation and resorption activity in a dose-dependent manner and displayed a trend for increased calcium deposits in MSC cultures. Numerous genes associated with osteoclast differentiation were differentially expressed in osteoclast precursor cells upon butyrate exposure. In vivo, antibiotic-treated mice showed reduced SCFA levels in the cecum, as well as a distinct gut microbiome composition. Furthermore, circulating proinflammatory TNF α, IL-17a, and IL-17f levels, and bone preserving osteoprotegerin (OPG), were increased in antibiotic-treated mice compared to controls. Antibiotic-treated mice also displayed a trend towards delayed bone healing as revealed by reduced mineral apposition at the defect site and higher circulating levels of the bone turnover marker PINP. Butyrate supplementation resulted in a lower abundance of monocyte/macrophages in the bone marrow, as well as reduced circulating proinflammatory IL-6 levels compared to antibiotic- and control-treated mice. In conclusion, this study supports our hypothesis that SCFAs, in particular butyrate, are important contributors to successful bone healing by modulating key cells involved in fracture healing as well as systemic inflammation and immune responses.